Purification and Characterization of 1-Aminocyclopropane-1-Carboxylic Acid N-Malonyltransferase from Tomato Fruit. - Martin, M. N. (1995)
1-Aminocyclopropane-1-carboxylic acid (ACC) can be oxidized to ethylene or diverted to the conjugate 1-(malonylamino)cyclopropane-1-carboxylic acid (MACC) by an ACC N-malonyltransferase. We developed a facile assay for the ACC N-malonyltransferase that resolved [14C]MACC from [14C]ACC by thin-layer chromatography and detected and quantified them using a radioisotope-imaging system. Using this assay, we showed that ACC N-malonyltransferase activity has developmental and tissue-specific patterns of expression in tomato (Lycopersicon esculentum) fruit. In the pericarp, activity was elevated for several days postanthesis, subsequently declined to a basal level, increased 3-fold at the onset of ripening, and again declined in overripe fruit. In the seed, activity increased throughout embryogenesis, maturation, and desiccation. Treatment of fruit with ethylene increased activity 50- to 100-fold in the pericarp. ACC N-malonyltransferase was purified 22,000-fold to a specific activity of 22,000 nmol min-1 mg-1 protein using ammonium sulfate precipitation, DyeMatrex Green A affinity, anion-exchange, Cibacron Blue 3GA affinity, hydrophobic interaction, and molecular filtration chromatography. Native and sodium dodecyl sulfate-denatured enzyme showed molecular masses of 38 kD, indicating that the enzyme exists as a monomer. The enzyme exhibited a Km for ACC of 500 [mu]M, was not inhibited by D- or L-amino acids, and did not conjugate [alpha]-aminoisobutyric acid or L-amino acids.